Disproportionate PFAS mass loading from landfill leachate: implications for biosolids management policy - Patrick M. D'Aoust; Benoit Barbeau; Sébastien Sauvé; Dwight Houweling (Journal of Environmental Management, 2026)

Association between anticholinergic and sedative medications and physical functioning: data from the Canadian longitudinal study on aging (CLSA) - Keren Pelen; Patrick Boissy; Karina Lebel; Alexandra Mayhew; Marla K Beauchamp; Lauren E Griffith; Megan E O’Connell; Sarah N Hilmer; Marie-Laure Baroud; Caroline Sirois; Frank Moriarty; Jean-Philippe Turcotte; et al. (European Journal of Clinical Pharmacology, 2026)

Stock Rebuilding in a Mixed‐Population Fishery Context: The Case of North Sea and Western Baltic Herring - Vanessa Trijoulet; Valerio Bartolino; Dorte Bekkevold; Benoit Berges; Henrik Mosegaard; Patrick Polte; Christoffer Moesgaard Albertsen (Fisheries Management and Ecology, 2026)
Managing and giving advice for mixed‐population fisheries of the same species can be challenging due to difficulties in predicting stock mixing, technical interactions, and in ensuring precautionary stock dynamics. Most fish species consist of several populations all of which need to be sustainably managed to preserve biodiversity and resilience to environmental changes, and to sustain productive fisheries. Mixing of populations of the same species with different productivity represents additional challenges for assessment and management. In such cases, there is a need to develop assessment and advice methods to consider mixed stocks and advise managers on fishing opportunities. In this study, we develop a framework including multifleet multi‐stock assessment models and forecasts where future stock dynamics depend on stock mixing, fleet‐specific fishing opportunities, and management in place. This framework is applied to the large North Sea herring stock and the overexploited western Baltic herring stock, which in part of their distribution areas are found to be mixed in both catches and surveys. The framework is used to investigate the trade‐offs between stock rebuilding and fishing opportunities in a mixed fishery. The study shows that spatial management implying transfer of quotas away from the areas where the stocks mix and towards the stock in good condition could help stock rebuilding without reducing overall fishing opportunities, however with a slower rebuilding rate compared to a more drastic fishery closure. The implementation of quota transfer should however consider the spatial relocation of fishing opportunities to avoid catch advice overshoot and inflated quotas.

Microbial Ecology of Mixotrophic Chain Elongation: Megasphaera spp. as Drivers of Medium‐Chain Carboxylate Production From H 2 , CO 2 , and Carboxylates - Grégoire B. L. Henry; Julien Tremblay; Benoit A. Stenuit; Patrick A. Gerin (Environmental Microbiology, 2026)
The production of medium‐chain carboxylates (MCC) by mixed culture fermentation of complex organic feedstocks is often constrained by the availability of reducing equivalents. Therefore, mixotrophic fermentation processes, which integrate diverse carbon and reducing equivalents sources, are gaining more attention. However, the microbial communities evolving in such complex environments, where organic and inorganic substrates interact, remain insufficiently understood. To identify the key microorganisms involved in mixotrophic MCC production, two bioreactors were initially fed with brewer's spent grain as organic feedstock and supplemented daily with H 2 and CO 2 as inorganic substrates. Time‐course analyses of net metabolite production rates and microbial community composition identified Megasphaera spp. (likely M. elsdenii and M. hexanoica ) as the main chain elongators in the system. The results suggest that these Megasphaera species metabolize short‐chain carboxylates, H 2 and CO 2 , with potential cross‐feeding interactions with acetogens (likely Clostridium ljungdahlii and Clostridium luticellarii ). The homoacetogenic acetate produced is subsequently elongated, likely by Megasphaera species, using H 2 and CO 2 as electron and carbon sources for production of elongated carboxylates. This study paves the way for the development of MCC production strategies that integrate organic waste valorization with direct CO 2 utilization, using H 2 as an electron donor, a process that aligns with low‐carbon‐footprint technologies.

Contrasting sources of dietary intake of cobalt and lead in the mining region of Katanga, DR Congo: a duplicate meal study - Trésor Carsi Kuhangana; Germain Kasongo Tengwa; Lore Roels; Eddy Mbuyu Ilunga; Taty Muta Musambo; Paul Musa Obadia; Tony Kayembe-Kitenge; Patrick D.M.C. Katoto; Célestin Banza Lubaba Nkulu; Erik Smolders; Peter Hoet; Benoit Nemery (Environmental Research, 2026)

Interactive effects of soil phosphorus and nitrogen availability on mycorrhiza-mediated nutrition in wheat - Margot Trinquier; Eric Lecloux; Bruno Patrick; Virginie Gasciolli; Claire Jouany; Christophe Roux; Benoit Lefebvre; Agnès Ardanuy (Plant and Soil, 2026)
Background and aims Arbuscular mycorrhizal fungi (AMF) play an essential role in plant nutrition in both natural and agro-ecosystems. However, how soil nutrient availability simultaneously regulates AMF diversity and contribution to plant nutrition, requires more attention. We hypothesised that the interaction between the availability of key soil macronutrients phosphorus (P) and nitrogen (N) regulates AMF contribution to wheat nutrition and that nutrient availability will simultaneously influence AMF community composition. Methods We tested this using a unique long-term P fertilisation trial, sampling wheat roots across two growing seasons. Expression of wheat mycorrhizal nutrient transporters was quantified by RT-qPCR and AMF communities were characterised by ITS2 metabarcoding. Complementary experiments under controlled conditions examined how the interaction between P and N regulates arbuscular mycorrhizal function in plant nutrition. Results Field-grown wheat showed campaign-specific effects of P fertilisation on AMF colonisation and nutrient transporter expression, which coincided with shifts in plant N status. Controlled experiments confirmed that colonisation depends on the limitation of either P or N, but that the regulation of peri-arbuscular phosphate, ammonium and nitrate transporters depended on the limiting nutrient. AMF communities also responded to soil P availability, with the genus Funneliformis consistently dominating under high P conditions. Conclusions Our findings demonstrate that P and N availability jointly shape root AMF communities and regulate their nutritive function in wheat. The combination of community profiling and mycorrhizal molecular markers provides a valuable approach for understanding the AMF contribution to plant nutrition across agroecosystems, and therefore can be used for optimising agroecological practices.

Muigaia, a new Paleotropical genus of Convolvulaceae - Simon Wachira Ngima; Vivian Kathambi; Samuel Paul Kagame; Sushant More; Lauren A. Eserman; Rafael Felipe de Almeida; Benoit Loeuille; Marc S. M. Sosef; Patrick Chalo Mutiso; Higor Antonio-Domingues; Lars W. Chatrou; Ana Rita Simões (Kew Bulletin, 2026)
Summary A new genus of Convolvulaceae, Muigaia , is here proposed and fully revised, including molecular phylogenetic analyses, comprehensive morphological and palynological descriptions, identification keys, distribution maps and conservation assessments. It is a strictly paleotropical genus, occurring in Tropical Africa, Madagascar, India and Australia, and remarkably absent from the Malesian region. It is distinctive for the markedly angular stems; deeply palmately lobed, irregularly dissected leaves; leaf-like stipules at the base of the petiole; muricate, verrucose or cristate sepals; a 3-globose stigma and a 6-valved capsule. A revision of the species involved in this complex has resulted in the recognition of a total of seven species, including five new combinations, one new name ( M. shimpalei ) and one newly described species ( M. australiana ), endemic to Australia. The tropical African specimens of M. coptica , in particular, exhibit a wide range of morphological variation and should be investigated in detail. We expect that, now that Muigaia has been phylogenetically and morphologically circumscribed, further revisionary studies could focus on improving the species delimitation, and likely result in the discovery of additional new species to science.

Geochemical characterisation of shallow pre-eruptive magma degassing at Marapi Volcano, Sumatra (Indonesia) - Charlotte Barrington; Hilma Alfianti; Ugan Boyson Saing; Patrick Allard; Philipson Bani; Fidel Costa; Benoit Taisne (Bulletin of Volcanology, 2026)
Marapi, Sumatra’s most persistently active volcano, exhibits frequent short-lived explosive activity and sporadic prolonged eruptions, often occurring with little to no detectable geophysical precursory signals. Despite advances in monitoring, our understanding of Marapi’s eruptive dynamics remains limited by a lack of information on its gas emissions. Here we present the first chemical dataset of Marapi’s volcanic gases measured using a Multi-component Gas Analyser System (Multi-GAS) from the rim of the active Verbeek crater during inter-eruptive activity in 2014 and 2018. Both datasets reveal gas compositions typical of magma-derived arc gases and a puffing degassing regime, with a periodicity of ~ 26 min in 2014 that decreased to 8–10 min in 2018. Notably, our 2018 measurements—performed just one month before two explosive outbursts on 27 April and 2 May 2018—show comparable SO₂/H₂S molar ratios (3.3 and 2.5) but a marked increase in total sulphur relative to CO 2 , resulting in a CO 2 /SO 2 ratio more than three times lower than in 2014. This chemical shift is consistent with shallower magma degassing preceding the April and May 2018 explosive activity. Our findings underscore the importance of regular, ideally continuous, gas monitoring at Marapi to better resolve magmatic processes that drive its explosive activity. We also report the first CO 2 /S T gas ratio measured for a Sumatran volcano, providing further evidence for sulphur-limited degassing along the Sunda Arc compared with other subduction zones.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

tRNA expression and modifications as critical components in the biology of blood-feeding arthropods - Melissa Kelley; Patrick A Limbach; Joshua B Benoit (Current Opinion in Insect Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Central-venous-catheter-related bloodstream infections in adult patients with sickle cell disease: a retrospective, two-centre study - Matthieu Holub; David Lebeaux; Patrick Grohs; Laure Joseph; Olivier Pellerin; Geoffrey Cheminet; Najiby Kassis; Salomé Abdellaoui; Jacques Pouchot; Brigitte Ranque; Jean Benoit Arlet; Emmanuel Lafont (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Regional invasion history and land use shape the prevalence of non‐native species in local assemblages - Daijun Liu; Franz Essl; Bernd Lenzner; Dietmar Moser; Philipp Semenchuk; Tim M. Blackburn; Phillip Cassey; Dino Biancolini; César Capinha; Wayne Dawson; Ellie E. Dyer; Benoit Guénard; et al. (Global Change Biology, 2024)
The ecological impact of non‐native species arises from their establishment in local assemblages. However, the rates of non‐native spread in new regions and their determinants have not been comprehensively studied. Here, we combined global databases documenting the occurrence of non‐native species and residence of non‐native birds, mammals, and vascular plants at regional and local scales to describe how the likelihood of non‐native occurrence and their proportion in local assemblages relate with their residence time and levels of human usage in different ecosystems. Our findings reveal that local non‐native occurrence generally increases with residence time. Colonization is most rapid in croplands and urban areas, while it is slower and variable in natural or semi‐natural ecosystems. Notably, non‐native occurrence continues to rise even 200 years after introduction, especially for birds and vascular plants, and in other land‐use types rather than croplands and urban areas. The impact of residence time on non‐native proportions is significant only for mammals. We conclude that the continental exchange of biotas requires considerable time for effects to manifest at the local scale across taxa and land‐use types. The unpredictability of future impacts, implied by the slow spread of non‐native species, strengthens the call for stronger regulations on the exchange of non‐native species to reduce the long‐lasting invasion debt looming on ecosystems' future.

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

A study on wildfire impacts on greenhouse gas emissions and regional air quality in South of Orléans, France - Chaoyang Xue; Gisèle Krysztofiak; Yangang Ren; Min Cai; Patrick Mercier; Frédéric Le Fur; Corinne Robin; Benoit Grosselin; Véronique Daële; Max R. McGillen; Yujing Mu; Valéry Catoire; et al. (Journal of Environmental Sciences, 2024)

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Occupational rhinitis and asthma in bakers: a cross-sectional study in the former Katanga province of DR Congo - Joseph Pyana Kitenge; Paul Musa Obadia; Trésor Carsi Kuhangana; Tony Kayembe-Kitenge; Patient Nkulu Banza; Lilian Nsenga Mukanda; Pascal Nawej Tshimwang; Patrick D. M. C. Katoto; Celestin Banza Nkulu Lubaba; Abdon Mukalay wa Mukalay; Benoit Nemery (International Archives of Occupational and Environmental Health, 2022)

Limitations of currently available in vitro oestrogenicity bioassays for effect-based testing of whole foods as the basis for decision making - Karma C. Fussell; Maricel Marin-Kuan; Emma Debon; Bastien Gentili; Delphine Morin-Rivron; Laure Poquet; Patrick Serrant; Flavia Badoud; Thomas Bessaire; Nicolas Christinat; Marion Ernest; Alexandre Félix; et al. (Food Additives & Contaminants: Part A, 2021)

Therapeutic prevention of COVID-19 in elderly: a case–control study - Frederic Blanc; Cedric Waechter; Thomas Vogel; Benoit Schorr; Catherine Demuynck; Catherine Martin Hunyadi; Maxence Meyer; Denata Mutelica; Nadjiba Bougaa; Samira Fafi-Kremer; Lidia Calabrese; Elise Schmitt; et al. (GeroScience, 2021)

The climatic debt is growing in the understorey of temperate forests: Stand characteristics matter - Benoit Richard; Jean‐Luc Dupouey; Emmanuel Corcket; Didier Alard; Frédéric Archaux; Michaël Aubert; Vincent Boulanger; François Gillet; Estelle Langlois; Sébastien Macé; Pierre Montpied; Thérèse Beaufils; et al. (Global Ecology and Biogeography, 2021)
Aim Climate warming reshuffles biological assemblages towards less cold‐adapted but more warm‐adapted species, a process coined thermophilization. However, the velocity at which this process is happening generally lags behind the velocity of climate change, generating a climatic debt the temporal dynamics of which remain misunderstood. Relying on high‐resolution time series of vegetation data from a long‐term monitoring network of permanent forest plots, we aim at quantifying the temporal dynamics – up to a yearly resolution – of the climatic debt in the understorey of temperate forests before identifying the key determinants that modulate it. Location France. Time period 1995–2017. Taxa studied Vascular plants. Methods We used the community temperature index (CTI) to produce a time series of understorey plant community thermophilization, which we subsequently compared to a time series of mean annual temperature changes over the same period and for the same sites. The direction and magnitude of the difference (i.e., the climatic debt) was finally analysed using linear mixed‐effect models to assess the relative contributions of abiotic and biotic determinants, including forest stand characteristics. Results We found a significant increase in CTI values over time (0.08–0.09 °C/decade), whereas the velocity of mean annual temperature changes was three times higher over the same period (0.22–0.28 °C/decade). Hence, the climatic debt increased over time and was greater in forest stands with higher basal area or older trees as well as under warmer macroclimate. By contrast, a greater frequency of anthropogenic disturbances decreased the climatic debt, while natural disturbances and herbivory had no impact. Conclusions Although often overlooked in understanding the climatic debt of forest biodiversity, changes in forest stand characteristics may modulate the climatic debt by locally modifying microclimatic conditions. Notably, the buffering effect of the upper canopy layer implies microclimate dynamics that may provide more time for understorey plant communities to locally adapt.

Mortality of marine mussels Mytilus edulis and M. galloprovincialis : systematic literature review of risk factors and recommendations for future research - Coralie Lupo; Stéphanie Bougeard; Véronique Le Bihan; Jean Louis Blin; Gwenhael Allain; Patrick Azéma; Fabienne Benoit; Christian Béchemin; Ismaël Bernard; Philippe Blachier; Léa Brieau; Morgane Danion; et al. (Reviews in Aquaculture, 2021)
The aim of this study was to summarise the literature reporting the risk factors for mortality in the mussel species Mytilus edulis and Mytilus galloprovincialis in order to identify potential science‐based solutions to prevent or mitigate mussel mortality outbreaks. We followed the PRISMA methodology: Preferred Reporting Items for Systematic Reviews and Meta‐Analyses. The studied corpus of 91 publications (114 studies) was highly heterogeneous with respect to the methodological approaches used to define or estimate mussel mortality and the related putative risk factors. Results showed that the mortality risk of both mussel species M. edulis and M. galloprovincialis varied across the seasons, increased with an elevated seawater temperature above a thermal threshold of 20 and 24°C, respectively, decreased by protecting mussels from predation, and was associated with the presence of pathogens in M. edulis . For M. galloprovincialis , using mussel spat from the same area where the farming is carried out and farming them together with another mussel species appears to reduce the mortality risk. However, for M. edulis , this could be achieved by using pure crosses and in particular mussel spat having a selected genotype. For wild bed conservation, sand accumulation and anthropogenic sedimentation should be minimised. Our analysis showed that current approaches to this research topic are limited and are unlikely to yield actionable evidence to identify mussel mortality prevention or mitigation strategies. Therefore, recommendations are offered to increase the ability of future eco‐epidemiological research to identify multiple exposures associated with mussel mortality, underpinned by standardised efforts and cooperative initiatives.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

Metabo-lipidomics of Fibroblasts and Mitochondrial-Endoplasmic Reticulum Extracts from ALS Patients Shows Alterations in Purine, Pyrimidine, Energetic, and Phospholipid Metabolisms - Charlotte Veyrat-Durebex; Céline Bris; Philippe Codron; Cinzia Bocca; Stéphanie Chupin; Philippe Corcia; Patrick Vourc’h; Rudolf Hergesheimer; Julien Cassereau; Benoit Funalot; Christian R Andres; Guy Lenaers; et al. (Molecular Neurobiology, 2019)

Observing System Evaluation Based on Ocean Data Assimilation and Prediction Systems: On-Going Challenges and a Future Vision for Designing and Supporting Ocean Observational Networks - Yosuke Fujii; Elisabeth Rémy; Hao Zuo; Peter Oke; George Halliwell; Florent Gasparin; Mounir Benkiran; Nora Loose; James Cummings; Jiping Xie; Yan Xue; Shuhei Masuda; et al. (Frontiers in Marine Science, 2019)

RECOTOX, a French initiative in ecotoxicology-toxicology to monitor, understand and mitigate the ecotoxicological impacts of pollutants in socioagroecosystems - Christian Mougin; Véronique Gouy; Vincent Bretagnolle; Julie Berthou; Patrick Andrieux; Patrick Ansart; Marc Benoit; Michaël Coeurdassier; Irina Comte; Cécile Dagès; Laurence Denaix; Sylvie Dousset; et al. (Environmental Science and Pollution Research, 2018)

Phylogeography, evolutionary history and effects of glaciations in a species ( Zootoca vivipara ) inhabiting multiple biogeographic regions - Jose L. Horreo; Maria L. Pelaez; Teresa Suárez; Merel C. Breedveld; Benoit Heulin; Yann Surget‐Groba; Tuula A. Oksanen; Patrick S. Fitze (Journal of Biogeography, 2018)
Aim During glaciations, the distribution of temperate species inhabiting the Northern Hemisphere generally contracts into southern refugia; and in boreo‐alpine species of the Northern Hemisphere, expansion from Northern refugia is the general rule. Little is known about the drivers explaining vast distributions of species inhabiting multiple biogeographic regions (major biogeographic regions defined by the European Environmental Agency). Here we investigate the fine‐scale phylogeography and evolutionary history of the Eurasian common lizard ( Zootoca vivipara ), the terrestrial reptile with the world's widest and highest latitudinal distribution, that inhabits multiple biogeographic regions. Location Eurasia. Methods We generated the largest molecular dataset to date of Z. vivipara , ran phylogenetic analyses, reconstructed its evolutionary history, determined the location of glacial refuges and reconstructed ancestral biogeographic regions. Results The phylogenetic analyses revealed a complex evolutionary history, driven by expansions and contractions of the distribution due to glacials and interglacials, and the colonization of new biogeographic regions by all lineages of Z. vivipara . Many glacial refugia were detected, most were located close to the southern limit of the Last Glacial Maximum. Two subclades recolonized large areas covered by permafrost during the last glaciation: namely, Western and Northern Europe and North‐Eastern Europe and Asia. Main conclusions In Z. vivipara, most of the glacial refugia were located in the South of their current distribution. Previous studies suggested the existence of Northern refuges, but the species' inability to overwinter on permafrost and the lack of genetic support suggest that the presence of a refugia in the north of the Alps is unlikely. This species currently inhabits boreo‐alpine climates and retracted during previous glaciations into southern refugia, as temperate species. Two clades exhibited enormous geographic expansion that started from two distinct glacial refugia. These phylogeographic patterns were highly congruent with those of Vipera berus . Together they suggest that glacial retraction, the location of the refugia and absence of competition may have promoted the enormous geographic expansion of two clades.

Consistency in coral skeletal amino acid composition offshore of Palau in the western Pacific warm pool indicates no impact of decadal variability in nitricline depth on primary productivity - Branwen Williams; Benoit Thibodeau; Yoshito Chikaraishi; Naohiko Ohkouchi; Andrew Walnum; Andréa G. Grottoli; Patrick L. Colin (Limnology and Oceanography, 2017)
The depth of the thermocline and associated nitricline in the western Pacific warm pool (WPWP) vary over time in response to changes in larger ocean‐atmosphere climate patterns. A shoaling of the nitricline in the WPWP brings nitrate‐rich seawater ( > 4 μ mol kg −1 ) above the base of the euphotic zone, stimulating primary productivity. Here, we test if decadal variability in the nitricline depth is driving changes in regional primary productivity and source nitrate dynamics. We use the nitrogen isotopic composition (δ 15 N) of amino acids in the skeleton of a proteinaceous coral collected from the base of the euphotic zone in the WPWP. In proteinaceous corals, as in most organic life, the δ 15 N of phenylalanine matches that of the ambient nitrate while the δ 15 N of trophic amino acids reflect subsequent trophic transfer of the nitrogen prior to incorporation into the coral's food, suspended particulate organic matter. Consistency of the trophic position of the coral calculated from the δ 15 N composition of the coral skeletal amino acids over its 56 yr lifespan suggest that decadal variability in nitricline depth and subsequent shifts in nitrate availability to the euphotic zone have not impacted primary productivity offshore of Palau in the WPWP. This is important when considering the current external forcing of Pacific Ocean climate patterns and the resulting impacts on the global carbon cycle in the Palau region of the WPWP.

Mercury accumulation and its effects on molecular, physiological, and histopathological responses in the peacock blenny Salaria pavo - Azza Naïja; Justine Marchand; Patrick Kestemont; Zohra Haouas; Ronny Blust; Benoit Chénais; Ahmed Noureddine Helal (Environmental Science and Pollution Research, 2016)

Biomarkers assessment in the peacock blenny Salaria pavo exposed to cadmium - Azza Naïja; Justine Marchand; Patrick Kestemont; Zohra Haouas; Ronny Blust; Benoit Chénais; Ahmed Noureddine Helal (Environmental Science and Pollution Research, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Metal binding to the N-terminal cytoplasmic domain of the PIB ATPase HMA4 is required for metal transport in Arabidopsis - Clémentine Laurent; Gilles Lekeux; Ashwinie A. Ukuwela; Zhiguang Xiao; Jean-Benoit Charlier; Bernard Bosman; Monique Carnol; Patrick Motte; Christian Damblon; Moreno Galleni; Marc Hanikenne (Plant Molecular Biology, 2016)

OsJAR1 is required for JA-regulated floret opening and anther dehiscence in rice - Yuguo Xiao; Yi Chen; Tatsiana Charnikhova; Patrick P. J. Mulder; Jeroen Heijmans; Angela Hoogenboom; Adamantia Agalou; Corinne Michel; Jean-Benoit Morel; Ludovico Dreni; Martin M. Kater; Harro Bouwmeester; et al. (Plant Molecular Biology, 2014)

Estimation of genealogical coancestry in plant species using a pedigree reconstruction algorithm and application to an oil palm breeding population - David Cros; Leopoldo Sánchez; Benoit Cochard; Patrick Samper; Marie Denis; Jean-Marc Bouvet; Jesús Fernández (Theoretical and Applied Genetics, 2014)

Evidence for strong seasonality in the carbon storage and carbon use efficiency of an Amazonian forest - Lucy Rowland; Timothy Charles Hill; Clement Stahl; Lukas Siebicke; Benoit Burban; Joana Zaragoza‐Castells; Stephane Ponton; Damien Bonal; Patrick Meir; Mathew Williams (Global Change Biology, 2014)
The relative contribution of gross primary production and ecosystem respiration to seasonal changes in the net carbon flux of tropical forests remains poorly quantified by both modelling and field studies. We use data assimilation to combine nine ecological time series from an eastern Amazonian forest, with mass balance constraints from an ecosystem carbon cycle model. The resulting analysis quantifies, with uncertainty estimates, the seasonal changes in the net carbon flux of a tropical rainforest which experiences a pronounced dry season. We show that the carbon accumulation in this forest was four times greater in the dry season than in the wet season and that this was accompanied by a 5% increase in the carbon use efficiency. This seasonal response was caused by a dry season increase in gross primary productivity, in response to radiation and a similar magnitude decrease in heterotrophic respiration, in response to drying soils. The analysis also predicts increased carbon allocation to leaves and wood in the wet season, and greater allocation to fine roots in the dry season. This study demonstrates implementation of seasonal variations in parameters better enables models to simulate observed patterns in data. In particular, we highlight the necessity to simulate the seasonal patterns of heterotrophic respiration to accurately simulate the net carbon flux seasonal tropical forest.

Cerebral oxygenation during hyperoxia-induced increase in exercise tolerance for untrained men - Kahina Oussaidene; Fabrice Prieur; Valerie Bougault; Benoit Borel; Regis Matran; Patrick Mucci (European Journal of Applied Physiology, 2013)

Aging of sensorimotor processes: a systematic study in Fitts’ task - Jean-Jacques Temprado; Rita Sleimen-Malkoun; Patrick Lemaire; Benoit Rey-Robert; Frédérique Retornaz; Eric Berton (Experimental Brain Research, 2013)

Extreme plasticity in life‐history strategy allows a migratory predator (jumbo squid) to cope with a changing climate - Henk‐Jan T. Hoving; William F. Gilly; Unai Markaida; Kelly J. Benoit‐Bird; Zachary W. ‐Brown; Patrick Daniel; John C. Field; Liz Parassenti; Bilin Liu; Bernardita Campos (Global Change Biology, 2013)
Dosidicus gigas (jumbo or Humboldt squid) is a semelparous, major predator of the eastern Pacific that is ecologically and commercially important. In the Gulf of California, these animals mature at large size (>55 cm mantle length) in 1–1.5 years and have supported a major commercial fishery in the Guaymas Basin during the last 20 years. An El Niño event in 2009–2010, was accompanied by a collapse of this fishery, and squid in the region showed major changes in the distribution and life‐history strategy. Large squid abandoned seasonal coastal‐shelf habitats in 2010 and instead were found in the Salsipuedes Basin to the north, an area buffered from the effects of El Niño by tidal upwelling and a well‐mixed water column. The commercial fishery also relocated to this region. Although large squid were not found in the Guaymas Basin from 2010 to 2012, small squid were abundant and matured at an unusually small mantle‐length ( D. gigas to rapidly adapt to and cope with El Niño. This ability is likely to be an important factor in conjunction with longerterm climate‐change and the potential ecological impacts of this invasive predator on marine ecosystems.

High-temperature infrared properties of forsterite - Myriam Eckes; Benoit Gibert; Domingos De Sousa Meneses; Mohammed Malki; Patrick Echegut (Physics and Chemistry of Minerals, 2013)

Carbon, nitrogen and Greenhouse gases budgets over a four years crop rotation in northern France - Benjamin Loubet; Patricia Laville; Simon Lehuger; Eric Larmanou; Christophe Fléchard; Nicolas Mascher; Sophie Genermont; Romain Roche; Rossana M. Ferrara; Patrick Stella; Erwan Personne; Brigitte Durand; et al. (Plant and Soil, 2011)

Pegylated Nanocapsules Produced by an Organic Solvent-Free Method: Evaluation of their Stealth Properties - Arnaud Béduneau; Patrick Saulnier; Nicolas Anton; François Hindré; Catherine Passirani; Holisoa Rajerison; Nicolas Noiret; Jean-Pierre Benoit (Pharmaceutical Research, 2006)

Evidence for proteins involved in prophenoloxidase cascade Eisenia fetida earthworms - Petra Procházková; Marcela Šilerová; Benoit Stijlemans; Marc Dieu; Petr Halada; Radka Josková; Alain Beschin; Patrick De Baetselier; Martin Bilej (Journal of Comparative Physiology B, 2006)

Zooplankton in the Schelde estuary, Belgium and the Netherlands: long-term trends in spring populations - Micky Tackx; Frédéric Azémar; Stéphanie Boulêtreau; Niels De Pauw; Kees Bakker; Benoit Sautour; Stéphane Gasparini; Karline Soetaert; Stefan Van Damme; Patrick Meire (Hydrobiologia, 2005)

Aid for aggregating the impacts in Life Cycle assessment - Valérie Benoit; Patrick Rousseaux (The International Journal of Life Cycle Assessment, 2003)

A Novel Phase Inversion-Based Process for the Preparation of Lipid Nanocarriers - Béatrice Heurtault; Patrick Saulnier; Brigitte Pech; Jacques-Emile Proust; Jean-Pierre Benoit (Pharmaceutical Research, 2002)

Low-Substrate Regulated Microaerophilic Behavior as a Stress Response of Aquatic and Soil Bacteria - Raja Mazumder; Holly C. Pinkart; Patrick S. Alban; Tommy J. Phelps; Robert E. Benoit (Current Microbiology, 2000)

Apolipoprotein A-I(R151C)Paris is defective in activation of lecithin:cholesterol acyltransferase but not in initial lipid binding, formation of reconstituted lipoproteins, or promotion of cholesterol efflux - Ulrike Daum; Claus Langer; Nicolas Duverger; Florence Emmanuel; Patrick Benoit; Patrice Patrice Denèfle; Ali Chirazi; Paul Cullen; P. Haydn Pritchard; Eric Bruckert; Gerd Assmann; Arnold von Eckardstein (Journal of Molecular Medicine, 1999)